Evaluation of Female Recipient Infertility and Donor Spermatogonial Purification for Germ Cell Transplantation in Paralichthys olivaceus - Yuqin Ren; Yuehong Tao; Zhaohui Sun; Yufen Wang; Weidong Li; Zhongwei He; Guixing Wang; Yucong Yang; Jilun Hou (Animals)
Since the advent of germ cell transplantation (GCT), it has been widely used in shortening the fish breeding cycle, sex-controlled breeding and the protection of rare and endangered fish. In this study, the effectiveness of female sterile recipient preparation and donor stem cell isolation and purification were comprehensively evaluated for spermatogonial stem cell transplantation (SSCT) in Paralichthys olivaceus. The best way to prepare sterile recipients was found to be giving three-year-old fish four intraovarian injections of busulfan (20 mg/kg body weight) combined with exposure to a high temperature (28 °C) after the spawning season compared with the two other ways, which induced apoptosis of most of the endogenous germ cells, resulting in shrinkage of the spawning plate and enlargement of the ovarian lumen. Further analysis showed that both the gonadosomatic index and germ-cell-specific vasa expression were significantly lower than those of the natural-temperature group before treatment (p < 0.05). A high percentage (>60.00%) of spermatogonial stem cells (SSCs) were obtained after isolation and purification and were transplanted into the prepared recipients. After three weeks of SSCT, the numbers of PKH26-labeled SSCs were increased in the ovaries of the recipients. These findings provide a basis for the establishment of an ideal SSCT technique using P. olivaceus females as the recipients, ultimately contributing to the efficient conservation of male germplasm resources and effective breeding.